Numerical Investigation of Mutually Injection-Locked Semiconductor Lasers for Direct IQ-Signal Generation - Nobuhide Yokota; Kazuya Komukai; Masato Yoshida; Hiroshi Yasaka (IEEE Photonics Journal, 2019)
A novel configuration of mutually injection-locked directly modulated lasers (DMLs) for generating in-phase quadrature (IQ) optical signals is proposed and numerically investigated by using rate equations. Two DMLs coupled with a high-Q ring resonator (Q = 2.2 × 105) are used for obtaining stable mutual-injection locking and suppression of the optical carrier component. First, conditions for mutual injection locking and modulation responses are investigated. Lasing frequencies are pulled toward the resonant frequency of the ring resonator due to the filtered mutual optical injections, and the pulling range is much broader than the transmission bandwidth of the ring resonator. Modulation bandwidth of the DMLs under the mutual-injection-locking condition is enhanced compared to that of the DMLs under the free-running condition. A resonant feature depending on the detuning condition appears in the modulation response, and it can be reproduced by the conventional injection-locking model. Next, optical-signal generations with quadrature phase shift keying (QPSK) format are tested under the assumption that the mutually injection-locked DMLs are driven by pseudo-random bit sequences. It is confirmed that 80-GBd QPSK modulation with back-to-back error vector magnitude of 32% can be achieved by using 8B/10B encoding.